Given: asub0 = 1 asub1 = 3
(asubn)^2 - asubn-1 * asubn+1 = (-1)^n for n greater or equal to 1
find asub3
i simplified it to (square root (n+(asubn-1)*(asubn+1) )= asubn
and i got asub2 = 8 and asub3 = 20.666...
Given: asub0 = 1 asub1 = 3
(asubn)^2 - asubn-1 * asubn+1 = (-1)^n for n greater or equal to 1
find asub3
i simplified it to (square root (n+(asubn-1)*(asubn+1) )= asubn
and i got asub2 = 8 and asub3 = 20.666...
Hello, stones44!
It is a rather confusing recurrence.
It took a while to straighten it out . . .
Solve forGiven: . -1)^n\quad\text{for }n \geq 1" alt="a_0 = 1,\;\;\;a_1 = 3.\;\;\;(a_n)^2 - (a_{n-1})\cdot(a_{n+1}) \:= \-1)^n\quad\text{for }n \geq 1" />
For , we have: .
For , we have: .